An emerging role for the mammalian Target of Rapamycin (mTOR) in 'pathological' protein translation: relevance to cocaine addiction - Christopher V Dayas; Doug W Smith; Peter R Dunkley (Frontiers Media S.A., 2012)
Complex neuroadaptations within key nodes of the brain's 'reward circuitry' are thought to underpin long-term vulnerability to relapse. A more comprehensive understanding of the molecular and cellular signalling events that subserve relapse vulnerability may lead to pharmacological treatments that could improve treatment outcomes for psychostimulant-addicted individuals. Recent advances in this regard include findings that drug-induced perturbations to neurotrophin, metabotropic glutamate receptor and dopamine receptor signalling pathways perpetuate plasticity impairments at excitatory glutamatergic synapses on ventral tegmental area (VTA) and nucleus accumbens (NAC) neurons. In the context of addiction, much previous work, in terms of downstream effectors to these receptor systems, has centered on the extracellular-regulated MAP kinase (ERK) signalling pathway. The purpose of the present review is to highlight the evidence of an emerging role for another downstream effector of these addiction-relevant receptor systems - the mammalian target of rapamycin complex 1 (mTORC1). mTORC1 functions to regulate synaptic protein translation and is a potential critical link in our understanding of the neurobiological processes that drive addiction and relapse behavior. The precise cellular and molecular changes that are regulated by mTORC1 and contribute to relapse vulnerability are only just coming to light. Therefore, we aim to highlight evidence that mTORC1 signalling may be dysregulated by drug-exposure and that these changes may contribute to aberrant translation of synaptic proteins that appear critical to increased relapse vulnerability, including AMPARs. The importance of understanding the role of this signalling pathway in the development of addiction vulnerability is underscored by the fact that the mTORC1 inhibitor rapamycin reduces drug-seeking in preclinical models and preliminary evidence indicating that rapamycin suppresses drug craving in humans.